Prognostic value of the 2017 World Health Organization Classification System for gastric neuroendocrine tumors: A single-center experience - Karakaş, Yusuf; Laçin, Şahin; Kurtulan, Olcay; Esin, Ece; Sunar, Veli; Sökmensüer, Cenk; Kılıçkap, Saadettin; Yalçin, Şuayib (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Gastric neuroendocrine tumors (G-NETs) are rare tumors, but their incidence is gradually increasing. Despite the existence of many classification systems, determining prognosis and planning treatment in patients with G-NETs remains a clinical challenge. In this study, the prognostic value of the World Health Organization (WHO) 2017 grading system and the effect of surgery on survival in low grade neuroendocrine tumors were investigated. Materials and Methods: G-NETs who were diagnosed between January 2000 and May 2017 were included in the study. Patients’ demographic characteristics, treatment details, and survival data were obtained from medical charts. Pathological samples were re-classified according to the WHO 2017 grading system. Results: Of the total 94 evaluated patients, 50 (53.2%) were classified with G1 NETs, 37(39.4%) with G2 NETs, 4(4.2%) with well-differentiated G3 NETs, and the remaining 3 patients with poorly differentiated G3 neuroendocrine carcinoma (NEC). The median follow-up time was 83.2 months. There was a statistically significant difference in 5-year progression free survival (PFS) between G1 tumors (100%) and G2 tumors (76%) (p<0.001). However, there was no statistically significant deference in 5-year overall survival rate (OS) for G1 (97%) and G2 (82%) tumors (p=0.141). When G2 and G1 NETs were compared according to their surgical approach, radical surgery was more frequently performed in patients with G2 tumors (p<0.001). However, radical surgery did not improve PFS in G1 and G2 NETs. Conclusion: The WHO 2017 NET classification system may have low prognostic value for determining the prognosis of patients with G1 and G2 tumors. Radical surgery for G1 and G2 NETs did not improve PFS in our study.